A multilocus molecular perspective on the systematics of the poorly known Northeast Indian colubrid snakes Blythia reticulata (Blyth, 1854), B. hmuifang Vogel, Lalremsanga & Vanlalhrima, 2017, and Hebius xenura (Wall, 1907) - Lalronunga, Samuel; Lalrinchhana, C.; Vanramliana, Vanramliana; Das, Abhijit; Gower, David J.; Deepak, V. (Zootaxa, 2020)
We provide the first molecular phylogenetic data for the following poorly known Northeast Indian snakes: Blythia reticulata and B. hmuifang, Hebius xenura, and Trachischium spp. Based on 1071 bp of cytb, 578 bp of nd4, 509 bp of 16s, 1000 bp of rag1 and 672 bp of cmos, we found support for a monophyletic Blythia being a member of Natricinae, most closely related to Trachischium. Hebius xenura is recovered as nested within species of the recently resurrected genus Herpetoreas, to which we transfer it.